The Effects of Digital Game-Based Learning in Technology-Oriented Course: A Case Study in the Biochemistry Department - Cengiz Gunduzalp (Journal of Education in Science, Environment and Health)
This study was done to find out what students thought about the variables of perceived control, perceived learning, perceived benefit, interest, motivation, affective components, attitude, behavioral components, and learning experience when using digital games in information and communication technologies courses. As a case study, the study was created. 30 students from the biochemistry department made up the study's research group. The tool for gathering data was a semi-structured interview form. Data analysis was done using the content analysis method. When the study's results were discussed, students claimed that playing digital games improved their perceptions of their level of control, interest in the subject, motivation, perceived value of the course, learning experiences, and learning facilitation. Students also mentioned that they felt a variety of positive emotions while using digital games, that they wanted to play them constantly and willingly, and that their attitudes had improved. To increase and enhance students' interest in the course, motivation, positive attitudes and emotions, desire, and learning experiences, digital games can be used in technology-focused courses.